SWITCHING LANGUAGES FOR POLITICAL FEAR, POWER AND ANGER IN DIGITALLY-SURVEILLANCED MULTILINGUAL FACEBOOK INTERACTION IN INDONESIA - Kamaludin Yusra (Masyarakat Linguistik Indonesia, 2022)
This paper examines how multilingual members of FB communities in Indonesia express fear, power, and anger with Covid19 and the government undertaking of its outbreak. John J. Gumperz’s (1982) and Dell Hymes’ (2005) sociolinguistic theories on identities and choices of languages in multilingual contexts and Herring, Stein, and Virtanen’s (2013) discourse theories on digitally-mediated intercultural communication is used as theoretical concepts and frameworks, building on FB as a site for intercultural contacts where language, culture, and political ideology are practised and selection of appropriate languages and forms is the main strategy for discursive safety. Data were collected by participant observations of FB interactions involving the Tadpoles (government supporters) and the Foxes (the oppositions) in Lombok, Indonesia. Twenty key players in each group were followed from January 2020 to August 2021. As the units of the analysis, words and sentences in the statuses and the comments of these players in in-group and out-group interactions were downloaded, transcribed, and translated into English. Analysis was done ethnographically by identifying contexts and contextualization cues in the translanguaging acts. The study shows that FB citizens, particularly the Tadpoles, used multiple linguistic competences in the online ideological battles as strategies to avoid possible legal consequences. English, Arabic, and local languages assumed to be inaccessible to the government officials and supporters were used as a means of covering disapprovals and discomforts with government policies. The study also shows how politically-marginalized speakers (the Foxes) make use of varied, multilingual linguistic competence as linguistic resources and symbolic capital to deconstruct and challenge hegemony of the government and its supporters (the Tadpoles).